STUDI TENTANG PEMBELAJARAN PROGRAM PENDIDIKAN KESETARAAN PAKET B DI PKBM HANDAYANI DESA TANJUANG BUNGO KECAMATAN SULIKI KABUPATEN 50 KOTA - Nursita, Yana; Maemunaty, Tity; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to determine equivalency education program learningpackages in PKBM Handayani Village Tanjuang Suliki Bungo District 50 District of theCity. This study was conducted Tanjuang Bungo village. This type of research isdescriptive qualitative research in the form of informant as much as 6 people. Dataobtained through observation, documentation, and interviews, and analyzed usingtriangulation techniques. The results showed the learning process in educationalequality in PKBM Handayani package is still not good .Keywords : learning , equality education program package B